Peran Kepala Sekolah Sebagai Manajer dalam Meningkatkan Kualitas Kinerja Guru di SD Negeri 012 Samarinda Kota - Yulia, Hana; Warman, Warman; Haryaka, Usfandi (Attractive : Innovative Education Journal, 2022)
This study aims to analyze the role of the principal as a manager in improving the quality of teacher performance. This study uses a qualitative approach with the type of case study research. This study's data sources came from informants, namely the principal and 1 teacher at the State Elementary School 012 Samarinda. They are collecting data using the method of observation, interviews, and documentation. The data collected was analyzed by the stages of data reduction, data display, verification, and confirmation of conclusions. The results of the research and discussion of research problems can be concluded that the role of the principal as a manager at SD Negeri 012 Samarinda Kota has a strong and significant influence in improving the quality of teacher performance. The role of the principal as a manager in improving teacher performance at SD Negeri 012 Samarinda Kota is going well. The principal has carried out his managerial role well, namely by carrying out direct action management activities starting from time management, administrative management, management of school rules and regulations. The principal as management involves elements of the school organization from teachers to other leaders in making and making decisions. This is reflected in the arrangement of activities led by the principal and involving the staff or stop below him, including teachers in supporting his performance. Keywords: Principal Roles, Principal Management, Teacher Performance